2012
DOI: 10.1200/jco.2011.39.5798
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Care for Family Caregivers of Patients With Cancer

Abstract: Recommendations for practice include development of standardized guidelines that address caregiver assessment, education, and resources; identification of "caregiver champions" in practice settings; provision of referrals to established support organizations for caregivers (eg, Cancer Support Community, Cancer Care); and collaboration among caregiving, professional, and cancer-related organizations to advocate policy and practice changes for family caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
423
0
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(453 citation statements)
references
References 59 publications
17
423
0
13
Order By: Relevance
“…A recent meta-analysis by Northouse et al [20] found that three types of interventions are typically offered to caregivers: Psychoeducational, skills training (coping, communication, and problem-solving skills), and therapeutic counseling. Although these interventions were found to have small to medium effects, they significantly reduced caregiver burden, enhanced coping behavior, increased self-efficacy (i.e., perceived confidence, preparation, and/or mastery to provide care), and improved aspects of QoL.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis by Northouse et al [20] found that three types of interventions are typically offered to caregivers: Psychoeducational, skills training (coping, communication, and problem-solving skills), and therapeutic counseling. Although these interventions were found to have small to medium effects, they significantly reduced caregiver burden, enhanced coping behavior, increased self-efficacy (i.e., perceived confidence, preparation, and/or mastery to provide care), and improved aspects of QoL.…”
Section: Recommendationsmentioning
confidence: 99%
“…Northouse et al suggested that development of standardized guidelines that address caregiver assessment, education, and resources; will help in improvement of care to the clients and also identification of "caregiver champions" in practice settings; provision of referrals to established support organizations for caregivers (e.g., cancer support community, cancer care); collaboration among caregiving, professional, and cancerrelated organizations to advocate policy and practice changes for family caregivers would provide better enhancement in nonprofessional care by caregivers [21].…”
Section: Recommendationsmentioning
confidence: 99%
“…Couples felt that the intervention helped men in particular to talk, as the structure of the questionnaire and the guided discussion gave permission for men to identify and respond to such issues. The couples in our study felt that the intervention enhanced their communication skills, which allowed for issues to be resolved and potentially drew couples closer together, something that most likely had a positive impact on their quality of life (Northouse et al, 2012a;Waldron et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…It is now well established that carers perform many vital roles to ensure patients are supported and safe whilst at home [4][5][6]. These roles require assistance from HCPs.…”
mentioning
confidence: 99%